Pemberdayaan Perempuan Di Era Digital Melalui Pelayanan Marketing Digital, Service Digital Dan Komunikasi Digital Menuju Desa Wisata Di Kecamatan Pulau Pinang - Merdasari, Iin; Antoni, Darius; Oktala, Rosananda (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research aims to find out strategies for empowering women in developing villages in the digital era through digital marketing, digital services, and digital communication towards tourist villages in Pulau Pinang District, 2. to find out the driving and inhibiting factors for women's empowerment in developing villages in the digital era through digital marketing, digital services and digital communications to tourist villages in Pulau Pinang District. This research uses primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews, and documentation. Data analysis techniques used include data analysis, data reduction, data presentation, verification, drawing conclusions, and testing data validity. This research shows that implementing government support to improve women's communication can help reduce village poverty. Government support for women's empowerment in tourist villages has been carried out. This activity aims to provide understanding and knowledge about how to market creative products in the digital era through digital marketing, digital services, and digital communications so that participants can apply them to increase sales of creative products in Pulau Pinang Village, Pulau Pinang District. Empowering Women Entrepreneurs in Pulau Pinang village aims to empower women entrepreneurs in the technology and digital fields. So that they can keep up with current developments where the world is entering industry 4.0, which uses more technology and digital capabilities; apart from that, people can get jobs without having to leave the village or the city, but by partnering with business owners who need their skills in the field of digital marketing.